The properties of bright globular clusters, ultra-compact dwarfs and dwarf nuclei in the Virgo core: hints on origin of ultra-compact dwarf galaxies (UCDs). Issue Volume 14:Issue S344(2019) (August 2018) - Liu, Chengze; Peng, Eric W.; Côté, Patrick; Zhang, Hong-Xin; Ferrarese, Laura; Jordán, Andrés; Mihos, J. Christopher; Muñoz, Roberto P.; Puzia, Thomas H.; Lançon, Ariane; Gwyn, Stephen; Cuillandre, Jean-Charles; et al.
Abstract: Based on the data from the Next Generation Virgo cluster Survey (NGVS), we statistically study the photometric properties of globular clusters (GCs), ultra-compact dwarfs (UCDs) and dwarf nuclei in the Virgo core (M87) region. We found an obvious negative color ( g - z ) gradient in GC system associate with M87, i.e. GCs in the outer regions are bluer. However, such color gradient does not exist in UCD system, neither in dwarf nuclei system around M87. In addition, we found that many UCDs are surrounded by extended, low surface brightness envelopes. The dwarf nuclei and UCDs show different spatial distributions from GCs, with dwarf nuclei and UCDs (especially for the UCDs with visible envelopes) lying at larger distances to the Virgo center. These results support the view that UCDs (at least for a fraction of UCDs) are more tied to dwarf nuclei than to GCs.